Ozone II: Characterization of In Situ Ozone Generation Using Diamond Electrodes - Heim, Carolin; Ureña de Vivanco, Mateo; Rajab, Mohamad; Glas, Karl; Horn, Harald; Helmreich, Brigitte; Letzel, Thomas (BrewingScience, 2011)
Ozone can be widely used for oxidation of diverse water constituents and mineralization of organic compounds and therefore for their elimination in drinking and process water as explained before in the review Ozone I: Characteristics/Generation/Possible Applications by Heim C. and Glas K., BrewingScience 2011 [1]. Electrolytic ozone generation in situ using boron-doped diamond electrodes is a relatively new and promising technology. The current article describes the formation of ozone directly from water with a DIACHEM® electrode. Ozone concentrations in water depend on the applied current on the one hand and on the water matrix on the other hand. The influence of organic and inorganic components on residual ozone concentrations in several water matrices was also investigated. The results form the basis to find reasonable applications of the described technology in the food and beverage industry.